2016
DOI: 10.1038/ncomms13295
|View full text |Cite
|
Sign up to set email alerts
|

Genome sequence and analysis of the Japanese morning glory Ipomoea nil

Abstract: Ipomoea is the largest genus in the family Convolvulaceae. Ipomoea nil (Japanese morning glory) has been utilized as a model plant to study the genetic basis of floricultural traits, with over 1,500 mutant lines. In the present study, we have utilized second- and third-generation-sequencing platforms, and have reported a draft genome of I. nil with a scaffold N50 of 2.88 Mb (contig N50 of 1.87 Mb), covering 98% of the 750 Mb genome. Scaffolds covering 91.42% of the assembly are anchored to 15 pseudo-chromosome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
137
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(143 citation statements)
references
References 68 publications
6
137
0
Order By: Relevance
“…Recent studies reported that high-quality genome sequence (Hoshino et al 2016) and the success of targeted mutagenesis by CRISPR/Cas9 system (Watanabe et al 2017) in I. nil. These information and technology would enable advanced carotenoid metabolic engineering so more progressive studies using I. nil will be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies reported that high-quality genome sequence (Hoshino et al 2016) and the success of targeted mutagenesis by CRISPR/Cas9 system (Watanabe et al 2017) in I. nil. These information and technology would enable advanced carotenoid metabolic engineering so more progressive studies using I. nil will be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In the eighth century, only one cultivar of I. nil had heard to be imported from China to Japan as a medicinal plant (Hoshino et al 2016). The original cultivar bore pale blue flowers containing cyanidins: anthocyanin compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, like in Arabidopsis, expression and activities of a number of Pharbitis genes and the physiological processes are presumed to exhibit circadian rhythms, those specifically affected by the clock system reset by the light-to-dark transition at dusk are still poorly understood because genes whose circadian expression was reported to be set by the dusk transition are currently limited to Pn FT1 and Pn FT2 . Unmasking genes whose circadian expression is set by lights-off by using genome-wide techniques such as RNAseq and knowledge on the recently uncovered whole genomic sequence in Pharbitis, 32 may help us to understand this physiological processes more deeply. Such a study may provide information on the significance of the dusk-set clock in adaptation to natural day/night cycles where the timing of sunrise and sunset annually changes with fluctuating day length.…”
mentioning
confidence: 99%
“…To test this hypothesis, we measured proanthocyanidin accumulation in CHS-D, CHI, and ANS loss-of-function morning glory mutants. We then predicted genes involved in proanthocyanidin biosynthesis using the published I. nil draft genome sequence (Hoshino et al 2016). Finally, we screened a large collection of I. nil lines and related Ipomoea species to isolate novel mutants exhibiting altered proanthocyanidin pigmentation in seed coats.…”
Section: Introductionmentioning
confidence: 99%